Leveraging Digital Marketing to Enhance The Competitiveness of Culinary Microenterprises: A Case Study From Rural Indonesia - Rizki, Nabila; Adinugraha, Hendri Hermawan; Gunawan, Ade (Maqrizi: Journal of Economics and Islamic Economics, 2025)
In the face of growing competition in the culinary sector, micro and small enterprises (MSEs) in developing countries face a dual imperative: digital transformation and market competitiveness. This study explores how digital marketing strategies can enhance the market performance of rural culinary MSEs, with a focused case study on Mr. Leman's Goat Satay stall in Central Java, Indonesia. Adopting a qualitative case study approach, data were collected through direct observations, semi-structured interviews, and documentation of digital activities. The findings reveal that while social media platforms—such as Instagram, Facebook, and TikTok—serve as effective tools for market expansion and consumer engagement, major constraints include limited digital literacy, inconsistent content management, and a lack of financial capital for sustained promotion. Despite these barriers, the presence of value-based communication, customer-centered content, and ethical marketing practices contributes significantly to brand loyalty and business resilience. This research contributes to the discourse on digital entrepreneurship by contextualizing digital strategy within Islamic ethical business frameworks, emphasizing the need for inclusive, adaptive, and socially responsible marketing approaches for rural MSEs.